Genistein supplementation to the quail: Effects on egg production and egg yolk genistein, daidzein, and lipid peroxidation levels - Akdemir, F.; Şahin, Kazım (Oxford Univ Press, 2009)
Genistein, a soy phytoestrogen, is a powerful antioxidant. In the present study, we investigated the effects of dietary genistein supplementation on Japanese quail (Coturnix coturnix japonica) laying performance and egg yolk contents of malondialdehyde (MDA), vitamin A, and vitamin E. Malondialdehyde is an indicator of lipid peroxidation, whereas vitamins A and E have antioxidant properties. Birds (n = 150; 5 wk old) were randomly assigned to 1 of 3 groups consisting of 50 birds (5 replicates of 10) and were fed a basal diet or the basal diet supplemented with either 400 or 800 mg of genistein/kg of diet. The experimental period lasted 90 d with a 17L:7D photo schedule. As antioxidant indices, yolk MDA and vitamin (A and E) concentrations were measured by HPLC. Dietary genistein supplementation (800 mg/kg) increased feed intake, egg production, egg weight, Haugh unit, shell thickness, and shell weight and improved feed efficiency at a greater extent than the other levels (0 and 400 mg/kg). Egg yolk genistein concentration was increased (P < 0.0001), whereas egg yolk MDA concentration was decreased (P < 0.0001) at the highest level of genistein supplementation. However, genistein supplementation did not affect egg yolk daidzein, vitamin A, and vitamin E levels. There was an inverse relationship between egg yolk genistein and MDA concentration (y = 0.02 x e(genistein), R-2 = 0.74, P < 0.0001). Results of the present study indicate that supplementing with dietary genistein (800 mg/kg) improved performance, egg quality, and egg yolk genistein content and decreased egg yolk MDA concentration in quail.
Keywords: genistein; egg yolk; malondialdehyde; Japanese quail